Partial removal of nail matrix in the treatment of ingrowing toe nail - (:unkn) unknown (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2008)
Objectives: Ingrowing toe nail is a frequent disorder of the foot. In this study, we evaluated the results of surgical treatment of ingrowing toe nail. Methods: Sixty-two patients (31 males, 31 females; mean age 38 years; range 11 to 72 years) with ingrowing toe nail underwent partial removal of the nail matrix according to the Winograd technique. The presenting complaints were pain, foul-smelling drainage, deformity, and difficulty in walking. According to the Heifetz's staging system, 18 patients had stage I, 23 patients had stage II, and 21 patients had stage III disease. Forty-four patients had active drainage due to an infectious process. The infected cases were operated on after improvement of inflammation by antibiotic treatment. One patient underwent excision of subungual exocytosis causing severe deformity of the toe. Time to return to work, time to recurrence, and patient satisfaction were evaluated. The mean follow-up period was 26 months (range 24 to 42 months). Results: Recurrence was seen in four patients (6.5%) within a mean of 4.2 months (range 3 to 7 months). The remaining patients returned to normal daily activities after a mean of 12 days (range 10 to 16 days). The mean time to work was five days (range 3 to 16 days). All but two patients who developed recurrences expressed satisfaction with surgery. None of the patients had deep infection or neurovascular complications. Conclusion: Partial removal of the nail matrix is associated with a very low recurrence rate and a higher rate of patient satisfaction.
Keywords: hallux/pathology; nail diseases; nails; ingrown/surgery; TOENAILS